The Effect of Red Dragon Fruit (Hylocereus polyrhizus) Rind Ethanol Extract on Collagen Deposition in The Liver of Menopause Model Rats - Kenjiro, Eduardo; Arijana, I Gusti Kamasan Nyoman; Sugiritama, I Wayan; Ratnayanti, I Gusti Ayu Dewi (E-Jurnal Medika Udayana; Vol 12 No 6 (2023): E-Jurnal Medika Udayana, 2023)
Background : Estrogen is a steroid hormone that is not only the primary sexual hormone in women, but also functions to protect the body from many damaging conditions, especially in the liver. Red dragon fruit ( Hylocereus polyrhizus ) rind is known to have a higher antioxidant potential than the fruit flesh and has the potential to be an alternative solution for this condition. Objective : To determine the effect of giving Hylocerus polyrhizus rind extract on collagen deposition in the livers of menopausal wistar rats. Methods : This randomized post-test only control group design study was conducted on in vivo experimental animals in the form of rats that had undergone the ovariectomy procedure and were randomly divided into three groups. Group P0 served as the control without intervention, P1 with the intervention of ethanol extract of red dragon fruit rind at a dose of 60 body weight/200gr/day, while P2 with the intervention at a dose of 90 body weight/200grBB/day. Results : Of the 30 mice divided into three groups, the mean area of collagen deposition was obtained in the P0 (24,130 ± 7,205), P1 (18,325 ± 4,221) and P2 groups (12,576 ± 3,739). The test results with One Way ANOVA found a significant difference with a value of p = 0.000189. The results of the LSD Post Hoc test found a significant difference in mean between the P0 and P2 groups (p = 0.00017). Conclusion : Administration of Hylocereus polyrhizus ethanol extract inhibited the expansion of collagen deposition in the treatment group's livers when compared to the control group's livers.